Expanding the European water Framework Directive indicators to address long-term climate change impacts on lakes using mechanistic lake models - L.M.V. Soares; M. Thouillot; V. Frossard; O. Desgué-Itier; C. Barouillet; Y. Baulaz; J.-C. Clément; I. Domaizon; J.-M. Dorioz; C. Goulon; J. Guillard; S. Jacquet; et al. (Ecological Indicators)
Climate change is altering lake ecosystems at an unprecedented rate, disrupting thermal regimes, biogeochemical cycles, and key ecological functions essential for human use such as drinking water, fisheries, and recreational activities. However, climate effects are often studied in isolation and over short time periods, which limits our ability to quantify the extent and speed of multifaceted ecological changes as well as our understanding of how lakes will evolve under climate change. We present a framework that integrates computer modelling, long-term forecasting, and multi-decadal limnological data to comprehensively evaluate 25 key metrics within the European Water Framework Directive related to lake functioning and ecological status through to 2100. Long-term projections of the effects of climate change were based on lake priority uses: 1) overall functioning, which supports aesthetic value and general attractiveness, 2) drinking water supply, and 3) stock of salmonids. Our findings reveal that although key thermal regime changes have already occurred, higher water temperatures will progressively push deeper salmonid habitat on both annual and seasonal scales. Favourable conditions for salmonids reproduction will exceed tolerance limits by 2050, and fishery management adjustments are needed. Conversely, drinking water supply should remain unaffected until 2100, assuming stable nutrient inputs and pollution levels. This approach offers a tool for forecasting climate change’s impacts on lakes, allowing decision-makers to anticipate measures to ensure long-term ecological and human benefits.